Accountability and Transparency in Regional Budget Management for Good Governance - Mursalin Mursalin; Khaeriyah Khaeriyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Regional budget management constitutes a critical foundation for achieving good governance in the era of decentralization and regional autonomy. This article comprehensively examines the pivotal role of accountability and transparency as essential instruments in enhancing the quality of regional budget governance. Employing a qualitative research methodology through systematic literature review and policy analysis, this study investigates the conceptual framework, implementation mechanisms, and practical implications of accountability and transparency principles in regional financial management. The findings reveal that robust implementation of accountability mechanisms—including financial reporting systems, internal and external oversight, and performance measurement—coupled with comprehensive transparency practices through information disclosure, public participation, and digital technology utilization, significantly contribute to strengthening institutional legitimacy, enhancing budget allocation efficiency, and preventing corruption. The research identifies that accountability is operationalized through multiple layers including legal compliance, procedural adherence, program effectiveness, and policy justification, while transparency manifests through open access to budget documents, participatory planning processes, and technology-enabled information systems. However, the study also uncovers substantial implementation challenges encompassing limited human resource capacity in financial management, inadequate inter-agency coordination, varying levels of public financial literacy and participation, and disparities in technological infrastructure between urban and rural areas. These challenges necessitate a multi-dimensional approach to reform. The article proposes evidence-based policy recommendations including systematic capacity building programs for government apparatus, strengthening regulatory frameworks with effective enforcement mechanisms, community empowerment through financial literacy initiatives, strategic investment in integrated digital platforms, and fostering collaborative partnerships among government institutions, legislative bodies, oversight agencies, civil society organizations, and citizens.